2013
DOI: 10.1080/13607863.2013.788997
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences of social interactions and their effects on subjective well-being among Japanese elders

Abstract: Objectives Gender differences of social interactions and their effects on subjective well-being among Japanese elders over three years were examined. Methods Repeated measurements of 498 elders over a three-year survey interval were obtained from a baseline mail survey and two- and three-year follow-up surveys. Outcomes were analyzed using Hierarchical Linear Modeling. Results Male elders were more likely to have a spouse and work at paid jobs, while female elders were likely to have more frequent contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 37 publications
3
11
0
1
Order By: Relevance
“…In a cross-classification analysis of equivalised income and frequency of meeting friends, we found that meeting friends was associated with frequency of laughter for both men and women. A previous study of older Japanese participants indicated that friendship was important for subjective well-being, 36 in accord with the notion that friendship decreases loneliness and anxiety, and increases happiness. 37 These findings suggest that meeting friends leads to more opportunities for laughter.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In a cross-classification analysis of equivalised income and frequency of meeting friends, we found that meeting friends was associated with frequency of laughter for both men and women. A previous study of older Japanese participants indicated that friendship was important for subjective well-being, 36 in accord with the notion that friendship decreases loneliness and anxiety, and increases happiness. 37 These findings suggest that meeting friends leads to more opportunities for laughter.…”
Section: Discussionsupporting
confidence: 57%
“… 18 Coming into contact with others is considered to be important to subjective well-being. 36 Thus, it is possible that wealthier people laugh more frequently because they have more opportunities to meet others. Therefore, we examined the influence of social relationship factors and family structure on the relationship between equivalised income and the frequency of laughter.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that casual conversation with others induces laughter, 39 and that friendship plays an important role in subjective well-being, loneliness, anxiety and happiness. 40 41 Therefore, it can be deduced that one of the main reasons for the association between social interactions and the frequency of laughter is that an increase in meeting others with a greater variety of social interactions leads to more opportunities to laugh. Laughter is one of the social activities between human relationships.…”
Section: Discussionmentioning
confidence: 99%
“…2011; Gow ym. 2013), elämään tyytyväisyyttä (Okabayashia & Hougham 2014), ja sosiaalisten suhteiden tiedetään vaikuttavan jopa kuolleisuuteen (Giles ym. 2005).…”
Section: Hoivakodit Tutkimusympäristönäunclassified